Computational Science and Its Applications - ICCSA 2016 16th International Conference, Beijing, China, July 4-7, 2016, Proceedings, Part III - Gervasi, Osvaldo; Murgante, Beniamino; Misra, Sanjay; Rocha, Ana Maria A.C; Torre, Carmelo M.; Taniar, David; Apduhan, Bernady O.; Stankova, Elena; Wang, Shangguang (Theoretical Computer Science and General Issues,, 2016)
The five-volume set LNCS 9786-9790 constitutes the refereed proceedings of the 16th International Conference on Computational Science and Its Applications, ICCSA 2016, held in Beijing, China, in July 2016. The 239 revised full papers and 14 short papers presented at 33 workshops were carefully reviewed and selected from 849 submissions. They are organized in five thematical tracks: computational methods, algorithms and scientific applications; high performance computing and networks; geometric modeling, graphics and visualization; advanced and emerging applications; and information systems and technologies.